Cognition and closed systems - Robert G. Bota (Mental Illness)
Mathematics is a-priory knowledge, a closed and self-sufficient system which con- nections with the material world are incidental rather than definitory. To make mathematics applicable and useful in a pragmatic sense one has to give meanings to numbers. The interplay between a-priori and a-posteriori thinking leads to useful applications of the former.